Sistematización de los proyectos de cooperación internacional en materia de conocimientos ancestrales ejecutados en comunidades indígenas de la provincia de Cotopaxi durante la última década del siglo XX y principios del siglo XXI - Caiza Chicaiza, Manuel Faustino (2012)
The research seeks to characterize the cultural context of the peoples and Indigenous nationalities in general until the characterization of the people Panzaleo for an approach to your ancestral knowledge. The context of international cooperation is then reviewed. To particularize in The cooperation executed in the province of Cotopaxi. Such as those carried out by the Fund Ecuadorian Populorium Progressio. With the Community Health Agents (ACS) and the Agricultural work in the so-called Integrated Agricultural Production System (SIPAs). It is also a question of showing the activities carried out by the International Plan in The educational field with children in the community Cuturivi Grande; On the other hand is The Holcim Foundation - Ecuador that works with communities that are located in the area Of influence of the cement plant. For this, the ancestral knowledge is analyzed from the international scope. National and local levels from a leader perspective. Leaders and beneficiaries. Through An interview of the life story realizes the impacts of heaven Interventions. A synthesis of objectives is then performed. Political, Guidelines and goals of the National Plan for Good Living 2009 - 2013 which give Directionality to approach knowledge, knowledge. Technologies and demonstrations Cultural activities. To end. Conclusions and possible actions to be implemented.